2017
DOI: 10.3847/1538-4357/aa7a11
|View full text |Cite
|
Sign up to set email alerts
|

The SAMI Galaxy Survey: Mass as the Driver of the Kinematic Morphology–Density Relation in Clusters

Abstract: We examine the kinematic morphology of early-type galaxies (ETGs) in eight galaxy clusters in the Sydney-AAO Multi-object Integral-field spectrograph Galaxy Survey. The clusters cover a mass range ofand we measure spatially resolved stellar kinematics for 315 member galaxies with stellar masses11.7 within 1 R 200 of the cluster centers. We calculate the spin parameter, λ R , and use this to classify the kinematic morphology of the galaxies as fast or slow rotators (SRs). The total fraction of SRs in the ETG po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 69 publications
17
94
0
Order By: Relevance
“…The Early Data Release (Allen et al 2015) provided data for 107 galaxies, while the first major data release (Green et al 2017) includes 772 galaxies. Science results from the SAMI survey so far include characterizing the galactic winds or extended diffuse ionizing gas in edge-on disk galaxies (Ho et al 2016), mapping the quenching of star formation proceeding from the outside in in dense environments (Schaefer et al 2017), and identifying stellar mass as the main variable affecting the fraction of ETGs that are slow rotators (Brough et al 2017).…”
Section: Overview Of the Survey Landscapementioning
confidence: 99%
“…The Early Data Release (Allen et al 2015) provided data for 107 galaxies, while the first major data release (Green et al 2017) includes 772 galaxies. Science results from the SAMI survey so far include characterizing the galactic winds or extended diffuse ionizing gas in edge-on disk galaxies (Ho et al 2016), mapping the quenching of star formation proceeding from the outside in in dense environments (Schaefer et al 2017), and identifying stellar mass as the main variable affecting the fraction of ETGs that are slow rotators (Brough et al 2017).…”
Section: Overview Of the Survey Landscapementioning
confidence: 99%
“…Earlier studies found a strong correlation between the stellar mass of a galaxy and its central kinematics. According to these studies the fraction of slow rotators increases significantly with stellar mass (Brough et al 2017;Jimmy et al 2013;Veale et al 2017). In order to extend this to the halo kinematics, we study the relation between the profile shape and stellar mass.…”
Section: Correlation With Stellar Massmentioning
confidence: 99%
“…When the mass distributions are carefully matched, the difference in  l out is not significant, with an Anderson-Darling test returning a probability = P 33% that the two distributions match. In a companion paper , we further compare the fast-and slow-rotator fractions as a function of local overdensity to compare with the recent literature (e.g., Cappellari 2016; Brough et al 2017;Veale et al 2017a). …”
Section: Dependence On Halo Massmentioning
confidence: 99%
“…We have long understood that rotational support s V (with V the maximum radial velocity and σ the stellar velocity dispersion) is a function of internal galaxy properties, with lower-mass ellipticals and S0s (earlytype galaxies) having more rotation than the most massive elliptical galaxies (e.g., Binney 1978;Davies et al 1983;Bender et al 1989;Franx & Illingworth 1990;Kormendy & Bender 1996). IFS studies have definitively shown that *L early-type galaxies typically have some net rotation , while the most massive elliptical galaxies tend to have little to no net rotation (e.g., Emsellem et al 2011;Houghton et al 2013;Raskutti et al 2014;Scott et al 2014;Brough et al 2017;Oliva-Altamirano et al 2017;Veale et al 2017aVeale et al , 2017b.…”
Section: Introductionmentioning
confidence: 99%